Changing Teacher Beliefs and Attitudes towards Inclusion in South Africa: Lessons from Collaborative Action Research - Makoelle, Tsediso (The Social Science Journal, 2014)
Worldwide there is a challenge to change teacher beliefs and attitudes towards implementing full inclusive education. This paper therefore reports on a collaborative action research process that sought to change teacher beliefs and conceptions about inclusion. The study was conducted qualitatively and adopted a critical emancipatory stance. Data were collected during action research stages through collaborative action research meetings, research diaries, participant observations and interviews. The data were then analysed using both group interpretative and inductive analytical frameworks. The findings indicated, inter alia, that while change through participation is crucial, changing teacher beliefs and attitudes about inclusion requires local context-relevant practices that teachers can relate to.
Keywords: educational change; Community of enquiry; inclusive education; Inclusive practice; Inclusive Learning Community; Research Subject Categories::SOCIAL SCIENCES::Social sciences::Education